Penerapan Pemberian Air Rebusan Daun Sirsak Terhadap Penurunan Skala Nyeri Pada Penderita Gout Arthritis - Andini, Marsella Ayuthia; Purborini, Nurul; Priyo, Priyo (Universitas Muhammadiyah Magelang, 2023)
Background: Gout Arthritis is an inflammatory process that occurs due to the deposition of uric acid crystals in the tissues around the joints which causes pain. If pain is not treated it will interfere with activities, so the therapy of giving soursop leaf boiled water is one of the non-pharmacological therapies that can be used to reduce the pain scale in the elderly with Gout Arthritis. Purpose: This study aims to apply soursop leaf decoction to pain in patients with Gout Arthritis. Method: The method used in this research is a case study with a sampling technique, namely purposive sampling. The sample taken in this study was an elderly 70 years old with Gout Arthritis with a scale of 5. Data collection in this study used participatory observation, interviews, and documentation methods. Results: The results of this study found that giving soursop leaf boiled water to respondents could reduce pain from a scale of 6 to a scale of 3 within seven days of intervention. Conclusion: Therapeutic administration of water decoction of soursop leaves can reduce Gout Arthritis pain. Suggestion: The therapy of giving soursop leaf boiled water can be applied to the elderly who have Gout Arthritis. (Arial Unicode MS9 pt, 1.0 space, spacing after 6pt)